Functionally inert HIV-specific cytotoxic T lymphocytes do not play a major role in chronically infected adults and children. - Goulder, P; Tang, Y; Brander, C; Betts, MR; Altfeld, M; Annamalai, K; Trocha, A; He, S; Rosenberg, E; Ogg, G; O'Callaghan, C; Kalams, SA; et al. (2000)
The highly sensitive quantitation of virus-specific CD8(+) T cells using major histocompatibility complex-peptide tetramer assays has revealed higher levels of cytotoxic T lymphocytes (CTLs) in acute and chronic virus infections than were recognized previously. However, studies in lymphocytic choriomeningitis virus infection have shown that tetramer assays may include measurement of a substantial number of tetramer-binding cells that are functionally inert. Such phenotypically silent CTLs, which lack cytolytic function and do not produce interferon (IFN)-gamma, have been hypothesized to explain the persistence of virus in the face of a quantitatively large immune response, particularly when CD4 help is impaired. In this study, we examined the role of functionally inert CTLs in chronic HIV infection. Subjects studied included children and adults (n = 42) whose viral loads ranged from <50 to >100,000 RNA copies/ml plasma. Tetramer assays were compared with three functional assays: enzyme-linked immunospot (Elispot), intracellular cytokine staining, and precursor frequency (limiting dilution assay [LDA]) cytotoxicity assays. Strong positive associations were observed between cell numbers derived by the Elispot and the tetramer assay (r = 0.90). An even stronger association between tetramer-derived numbers and intracellular cytokine staining for IFN-gamma was present (r = 0.97). The majority (median 76%) of tetramer-binding cells were consistently detectable via intracellular IFN-gamma cytokine staining. Furthermore, modifications to the LDA, using a low input cell number into each well, enabled LDAs to reach equivalence with the other methods of CTL enumeration. These data together show that functionally inert CTLs do not play a significant role in chronic pediatric or adult HIV infection.